2016
DOI: 10.1002/jcb.25514
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Histamine 1 Receptor Antagonist Cetirizine on the Osteoporotic Phenotype in H+/K+ATPase Beta Subunit KO Mice

Abstract: Epidemiological studies suggest increased fracture risk in patients using proton pump inhibitors (PPIs). We have previously shown that the H(+) /K(+) ATPase beta subunit knockout (KO) mouse, which is a model of PPI-use, have lower bone mineral density (BMD) and impaired bone quality compared to wild type (WT) mice. Like PPI users, these KO mice display elevated gastric pH and hypergastrinemia, which in turn stimulates gastric histamine release. Previous studies have suggested a negative effect of histamine on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…29 Treatment with cetirizine (a 2 nd generation H1-antihistamine) did not have any impact on BMD values or bone tissue properties in H(+)/K(+) ATPase β subunit knockout (KO) mice, which are genetically modified to have high histamine levels leading to secondary decreases in BMD. 11,31 Recently, Folwarczna et al 14 administered loratadine (a 2 nd generation H1-antihistamine) to ovariectomized and non-ovariectomized rats with bone metabolism disorders. Short-term loratadine administration significantly improved bone metabolism and biomechanical bone properties in the non-ovariectomized rats.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…29 Treatment with cetirizine (a 2 nd generation H1-antihistamine) did not have any impact on BMD values or bone tissue properties in H(+)/K(+) ATPase β subunit knockout (KO) mice, which are genetically modified to have high histamine levels leading to secondary decreases in BMD. 11,31 Recently, Folwarczna et al 14 administered loratadine (a 2 nd generation H1-antihistamine) to ovariectomized and non-ovariectomized rats with bone metabolism disorders. Short-term loratadine administration significantly improved bone metabolism and biomechanical bone properties in the non-ovariectomized rats.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] The presence of H1-histamine receptors on both osteoblasts and osteoclasts has been confirmed. 11 Pro-inflammatory cytokines, e.g., interleukin-1, interleukin-6 and TNF-α, increase osteoclast activity through the RANK/RANKL/OPG pathway and inhibit osteoblast activity. Prostaglandins may stimulate both bone formation and bone resorption.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore loratadine, often prescribed to allergic children, is able to slightly but significantly affect at high dose the development of the skeletal system in rapidly growing rats [56]. However, Aasarød et al found increased levels of histamine in an animal model of gastric hypoacidity and hypergastrinemia associated with reduced bone quality and mechanical bone strength while the H1R antagonist cetirizine did not show to be beneficial on bone parameters [57][58][59][60].…”
Section: Histaminementioning
confidence: 99%
“…In vitro and in vivo experimental studies demonstrated that histamine is involved in the regulation of bone metabolism 813. Expression of histamine H 1 and H 2 receptors in bone cells (osteoblasts and osteoclasts) is well documented,810,14 and histamine is synthesized in osteoclast precursors 8. Histamine increases bone resorption both directly, acting on osteoclast precursors and osteoclasts, and indirectly, by stimulation of the RANKL expression in osteoblasts 810.…”
Section: Introductionmentioning
confidence: 99%